2021
DOI: 10.1021/acs.energyfuels.1c00227
|View full text |Cite
|
Sign up to set email alerts
|

Simulations and Optimization of a Reduced CO2 Emission Process for Methanol Production Using Syngas from Bi-reforming

Abstract: A low CO2 emission process for methanol production using syngas generated by combined H2O and CO2 reforming with CH4 (bi-reforming) is proposed in this work. A detailed process model was developed using Aspen Plus. The operating conditions of the bi-reforming and methanol synthesis were derived from a detailed sensitivity analysis using plug flow reactor models with Langmuir–Hinshelwood–Hougen–Watson (LHHW) kinetics. A molar feed ratio of CH4:CO2:H2O of 1:1:2, instead of conventional 3:1:2 in the bi-reforming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…have successfully converted carbon dioxide to valuable hydrocarbons. However, the conversion efficiency in electrocatalysis and photocatalysis is relatively low. In comparison, thermocatalysis has been maturely developed for decades and has been considered the most applicable technique because of the high conversion efficiency. , Methane, another main contributor to the greenhouse effect, is abundant in natural gas and shale gas. It is also a carbon resource that can be used for value-added energy fuel production. Because of the difficult C–H activation by photocatalysis and electrocatalysis under mild conditions, the methane conversion rate is rather slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have successfully converted carbon dioxide to valuable hydrocarbons. However, the conversion efficiency in electrocatalysis and photocatalysis is relatively low. In comparison, thermocatalysis has been maturely developed for decades and has been considered the most applicable technique because of the high conversion efficiency. , Methane, another main contributor to the greenhouse effect, is abundant in natural gas and shale gas. It is also a carbon resource that can be used for value-added energy fuel production. Because of the difficult C–H activation by photocatalysis and electrocatalysis under mild conditions, the methane conversion rate is rather slow.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, thermocatalysis has been maturely developed for decades and has been considered the most applicable technique because of the high conversion efficiency. 6,7 Methane, another main contributor to the greenhouse effect, is abundant in natural gas and shale gas. It is also a carbon resource that can be used for value-added energy fuel production.…”
Section: Introductionmentioning
confidence: 99%
“…They found that higher CO 2 in the feed did not impact the conversion of CH 4 , increased the CO 2 conversion, and decreased the H 2 /CO ratio in the product stream. Recently, Acquarola et al 19 used a feed ratio of 1:1:2 in the bi-reforming step and reported significantly lower CO 2 emission in their process. Heat integration or heat recovery in such a two-step process is extremely critical to the reduction of CO 2 emission in the process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, a few studies 5,15,20,21 considered the conditions of feed components (CO 2 , H 2 O, and CH 4 ) to be at the reactor inlet temperature or pressure or both. In reality, CH 4 is typically available at high pressure and H 2 O is available at ambient conditions as considered by Acquarola et al 19 and Nguyen and Zondervan. 13 In this two-step process, it is also critical to adjust the CO 2 concertation in the gas stream coming out of the bi-reforming step.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation